2008
DOI: 10.1093/nar/gkn591
|View full text |Cite
|
Sign up to set email alerts
|

MECP2 genomic structure and function: insights from ENCODE

Abstract: MECP2, a relatively small gene located in the human X chromosome, was initially described with three exons transcribing RNA from which the protein MeCP2 was translated. It is now known to have four exons from which two isoforms are translated; however, there is also evidence of additional functional genomic structures within MECP2, including exons potentially transcribing non-coding RNAs. Accompanying the recognition of a higher level of intricacy within MECP2 has been a recent surge of knowledge about the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 102 publications
(180 reference statements)
0
40
0
1
Order By: Relevance
“…The authors also reported the presence of two negative regulatory elements [(−309 to −370) and (−553 to −681)] and one positive regulatory element (−847 to −1,071) in the promoter region upstream of the MECP2 exon 1 (−1,071 to +9), activity of which are cell-type specific (Liu and Francke 2006). Later on, another study on the encyclopedia of DNA elements (ENCODE) [http://genome.ucsc.edu/] for MECP2/Mecp2 gene showed that the same promoter region and upstream of that region harbors binding sites for transcription factors such as SP1, SP3, TAP1, RNA Pol II, C/EBP, E2F1 and CTCF, binding of which were confirmed by chromatin immunoprecipitation experiments in different cell lines (Singh et al 2008). Adachi et al, in 2005 reported that only a segment of Mecp2 promoter (−677/−56) is essential to drive the Mecp2 expression in neuronal cell lines and cortical neurons (Adachi et al 2005).…”
Section: Promoter Elementsmentioning
confidence: 88%
See 1 more Smart Citation
“…The authors also reported the presence of two negative regulatory elements [(−309 to −370) and (−553 to −681)] and one positive regulatory element (−847 to −1,071) in the promoter region upstream of the MECP2 exon 1 (−1,071 to +9), activity of which are cell-type specific (Liu and Francke 2006). Later on, another study on the encyclopedia of DNA elements (ENCODE) [http://genome.ucsc.edu/] for MECP2/Mecp2 gene showed that the same promoter region and upstream of that region harbors binding sites for transcription factors such as SP1, SP3, TAP1, RNA Pol II, C/EBP, E2F1 and CTCF, binding of which were confirmed by chromatin immunoprecipitation experiments in different cell lines (Singh et al 2008). Adachi et al, in 2005 reported that only a segment of Mecp2 promoter (−677/−56) is essential to drive the Mecp2 expression in neuronal cell lines and cortical neurons (Adachi et al 2005).…”
Section: Promoter Elementsmentioning
confidence: 88%
“…Chromatin immunoprecipitation results shown in ENCODE demonstrate unique distribution of histone PTMs throughout the MECP2/Mecp2 gene. For example, active histone marks H3K4me2 and H3K4me3 are clustered around the transcription start sites of MECP2/Mecp2 [ (Singh et al 2008) and (http://genome.ucsc.edu/)]. Further showing the role of histone acetylation in regulating MECP2 expression in glioma cells, inhibition of HDAC activity by valproic acid induced MECP2 transcript expression in a time-dependent manner (Kim et al 2008).…”
Section: Histone Posttranslational Modificationsmentioning
confidence: 99%
“…However, MECP2 has a higher level of complexity than originally believed [29]. MECP2 has been coimmunoprecipitated with the silencing mediator for retinoid and TH receptors [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the MBD tailor a wedge-shaped molecular structure as shown in figure 4.1.It contains a hydrophobic pocket having the side chains Tyr123 and Ile125 present on the beta-sheet face is thesite of contact with the Methyl groups of the cytosine residues (Wakefieldet al, 1999).The N-terminus of the MBD consist of amino acid identical the HMG (high mobility group proteins) that regulate DNA activities such as transcription, translation etc. Recently the interaction between the N-terminal region and theRepressive Chromatin Regulator Heterochromatin protein 1 (HP1) has been shown which is the key factor in formation of transcriptionally inactive heterochromatin (Singh et al, 2008). …”
Section: The Methyl-cpg Binding Domain (Mbd)mentioning
confidence: 99%